The implementation of new standards for Allium aflatunense flowering onion - L.V. Pavlov; O.T. Paraskova; A.F. Agafonov; M.V. Dubova (Овощи России, 2009)
Allium aflatunense has been studied at All-Russian Research Institute of Vegetable Breeding and Seed Production as a new plant culture that has high adaptability, acceptable qualities so that it can be well introduced to breeding program for middle belt of Russia. Samson cultivar has been selected as a result of breeding and joined efforts of the laboratory of standardization and metrology with the onion research group at All-Russian Research Institute of Vegetable Breeding and Seed Production. There were worked out descriptors for traits and sowing recommendations.